(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This study evaluates the behaviors of six coaches and 64 indoor soccer athletes of the Sub 9 and Sub 15 categories regarding the anti-sporting and fair play behaviors. The matches and the coaches’ comments were recorded and a copy of the docket of the match was taken. Then the athletes’ faults contact, anti-sportive and fair play behavior were registered as well as the coaches’ behavior regarding the athletes’ behavior. It could be noted a greater occurrence of fair play behaviors among the athletes of the Sub 15 category than from the ones of Sub 9. The rate of anti-sporting behaviors was low in both categories, being the gravity of these behaviors smaller to Sub 9. The coaches of both categories were indifferent to the antisporting and fair play behaviors of their athletes. The specific contingencies of the modality might contribute to alter the frequency of such behavior in competition contexts. Keywords: Sport Psychology. Athletes and Coaches. Moral Behavior.